METHODS FOR DETERMINING THE COMPLEXITY OF HUMAN ORGANS AND TISSUES - Bahramov Muhammadali Eraliyevich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Fractal geometry can analyze the complexity of human organs and tissues on different scales and be diagnosed on this basis. The complex structure of many biological systems, such as the lungs, liver and brain, can be seen in fractal salinity organs and self-similarity at different levels of the body. For example, describing the branching structure of a bronchial tree in the lungs using fractal geometry, small bronchioles exhibit similarities to large bronchi. This fractal structure ensures effective oxygen exchange and helps to maximize the surface area available for oxygen exchange. Likewise, the branched structure of blood vessels in the cardiovascular system manifests fractal structures, with smaller vessels having a structure similar to larger ones. This fractal structure is important for the efficient supply of nutrients and oxygen to the body's tissues.